2015
DOI: 10.1038/modpathol.2014.126
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal tract spindle cell lesions—just like real estate, it's all about location

Abstract: Interpretation of gastrointestinal tract mesenchymal lesions is simplified merely by knowing in which anatomic layer they are usually found. For example, Kaposi sarcoma is detected on mucosal biopsies, whereas inflammatory fibroid polyp is nearly always in the submucosa. Gastrointestinal stromal tumors (GISTs) are generally centered in the muscularis propria. Schwannomas are essentially always in the muscularis propria. Mesenteric lesions are usually found in the small bowel mesentery. Knowledge of the favored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 60 publications
0
34
0
1
Order By: Relevance
“…Ancillary immunohistochemical characterization of upper GI spindle cell proliferations may trigger definitive rather than descriptive diagnoses on small samples (Table ) and may allow for separation of GISTs, leiomyomata, schwannomas, carcinoid tumors, and PFs. It should also be noted that other spindle cell lesions, including but not necessarily limited to desmoid‐type fibromatoses, inflammatory fibroid polyps, and solitary fibrous tumors may enter the differential diagnosis . The upper GI tract is less frequently biopsied in comparison to other sites in larger EUS series; however, EUS with FNA and/or core biopsy is known to be an effective modality for the diagnosis of upper tract submucosal and spindle cell lesions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancillary immunohistochemical characterization of upper GI spindle cell proliferations may trigger definitive rather than descriptive diagnoses on small samples (Table ) and may allow for separation of GISTs, leiomyomata, schwannomas, carcinoid tumors, and PFs. It should also be noted that other spindle cell lesions, including but not necessarily limited to desmoid‐type fibromatoses, inflammatory fibroid polyps, and solitary fibrous tumors may enter the differential diagnosis . The upper GI tract is less frequently biopsied in comparison to other sites in larger EUS series; however, EUS with FNA and/or core biopsy is known to be an effective modality for the diagnosis of upper tract submucosal and spindle cell lesions .…”
Section: Resultsmentioning
confidence: 99%
“…They are usually detected incidentally, including but not necessarily limited to desmoid-type fibromatoses, inflammatory fibroid polyps, and solitary fibrous tumors may enter the differential diagnosis. [56][57][58][59][60][61][62] The upper GI tract is less frequently biopsied in comparison to other sites in larger EUS series; however, EUS with FNA and/or core biopsy is known to be an effective modality for the diagnosis of upper tract submucosal and spindle cell lesions. [63][64][65][66] Recent studies have suggested higher diagnostic accuracy with newer EUS coring needles, as well as the advantage of establishing diagnoses with fewer passes.…”
Section: Schwannomamentioning
confidence: 99%
“…GISTs are occasionally diagnosed on mucosal biopsy if the lesion is too aggressive to have invaded mucosa. 2 GISTs are most common in adults of 50-60 years and about 25% of GISTs are malignant, representing almost 1% of all GI malignancies. 7 According to the location, oesophageal GISTs are rare, 50-70% are seen in the stomach; 25-40% involve the small intestine and <10% are colorectal.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients are in the age group of 60 and 80 years. 2,10 Clinical presentation is based on the site of the tumour thus the small intestinal examples can lead to intussusception or obstruction, and gastric examples are found in patients with pain, nausea, and vomiting. 11 Inflammatory fibroid polyps were reported in a family in which three generations of women had these 'Devon polyposis' lesions.…”
Section: Discussionmentioning
confidence: 99%
“…IFP, a benign mesenchymal neoplasm of the stomach, small bowel, and, occasionally, the colon, is often associated with an inflammatory infiltrate rich in eosinophils (Figure ). IFPs are centred in the submucosa, but can infiltrate the overlying lamina propria, so that superficial biopsies of the lesion might result in confusion with an eosinophilic disorder.…”
Section: Secondary Causes Of Eosinophilia In the Gi Tractmentioning
confidence: 99%